Embodied Faith: Agency of Postmenopausal Muslim Women and Narratives of Piety in Religious Practices - Nabillah Kurniati; Livi Husnia Aidatul Fitroti (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study aims to examine how postmenopausal Muslim women exercise pious agency through embodied religious practices and how they construct narratives of piety within socio-religious spaces. The cessation of menstruation places postmenopausal women under the same ritual obligations as men, creating distinctive religious experiences shaped by age, bodily transformation, and reproductive history. Drawing on a qualitative approach that combines phenomenology and narrative analysis, this research engages Saba Mahmood’s concept of agency within the politics of piety to explore how religious devotion is lived, interpreted, and sustained by postmenopausal women. Data were collected through in-depth interviews and observations of women’s participation in both domestic and public religious practices. The findings demonstrate that postmenopausal Muslim women exhibit strong commitment to daily worship and religious community activities, particularly in mosques and study circles. Piety is understood not merely as ritual compliance, but as a continuous ethical practice emerging from embodied experience, spiritual education, and acceptance of the postmenopausal body. This study argues that women’s piety is shaped by the intersection of ritual habitus, reproductive experience, and social interaction, positioning postmenopausal women as active moral agents rather than passive subjects. Ultimately, the article contributes to gender-sensitive Islamic studies by highlighting embodied faith as a source of religious agency and socio-religious empowerment.